Kepemimpinan KH. Achmad Muzakki Syah, Pengasuh Pondok Pesantren Al-Qodiri Jember: The Leadership of KH. Achmad Muzakki Syah, Caretaker of Al-Qodiri Islamic Boarding School, Jember - M. Walid (Fenomena, 2007)
The rapid pace of globalization demands transforming leadership systems in Indonesian Islamic boarding schools (pesantren), shifting from hereditary models toward more adaptive and collective frameworks. This study examines the leadership style of KH. Ach. Muzakki Syah, the leader of Al-Qodiri Pesantren in Jember, and its influence and contributing factors. Using a qualitative phenomenological approach, data were collected through observation, in-depth interviews, and documentation, then analyzed using grounded research methods. The findings reveal that KH. Ach. Muzakki Syah employs a spiritual leadership model rooted in religious exemplarity, integrating charismatic and democratic elements while adopting autocratic leadership on principle-based issues such as santri obligations and pesantren ethics. His leadership significantly influences a broad spectrum of society, including farmers, traders, local officials, governors, ministers, and even the President of Indonesia. The growth of the pesantren from 9 students in 1976 to 4,000 in 2006, alongside the establishment of formal educational institutions and the widespread manaqib congregation network, demonstrates this influence. Key supporting factors include belief, istiqomah (consistency), sincerity, love, patience, and tangible spiritual outcomes. This study recommends that pesantren adopt shared leadership models to ensure sustainability and relevance in the modern era. Arus globalisasi yang cepat menuntut transformasi sistem kepemimpinan di pesantren Indonesia, dari model pewarisan herediter menuju pola yang lebih adaptif dan kolektif. Penelitian ini membahas tipe kepemimpinan KH. Ach. Muzakki Syah, Pengasuh Pondok Pesantren Al-Qodiri Jember, serta mengkaji pengaruh dan faktor-faktor yang memengaruhinya. Menggunakan pendekatan kualitatif fenomenologis, data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, lalu dianalisis dengan metode grounded research. Hasil penelitian menunjukkan bahwa KH. Ach. Muzakki Syah menerapkan tipe kepemimpinan spiritual religius yang mengedepankan keteladanan, memadukan tipe kharismatik dan demokratis, serta menggunakan tipe otokratis untuk persoalan prinsip seperti kewajiban santri dan etika kepesantrenan. Kepemimpinannya berpengaruh luas, mencakup petani, pedagang, pejabat daerah, gubernur, menteri, hingga Presiden. Pertumbuhan pesantren dari 9 santri (1976) menjadi 4.000 santri (2006), serta berdirinya lembaga formal dan jaringan jamaah manaqib, menjadi bukti nyata pengaruh tersebut. Faktor pendukung meliputi keyakinan, istiqomah, keikhlasan, kesederhanaan, cinta, kesabaran, dan bukti nyata doa yang terkabul. Penelitian ini merekomendasikan penerapan kepemimpinan kolektif (shared leadership) di pesantren untuk menjamin keberlanjutan dan relevansi di era modern.